Management of Euschistus heros with the release of Telenomus podisi in soybean in Brazil - Ramos, Gabryele Silva [UNESP]; Dalbianco, Alessandro Bandeira [UNESP]; Santos, Daniel Mariano [UNESP]; de Lima Alvarez, Daniel [UNESP]; de Oliveira, Regiane Cristina [UNESP] (Springer Nature, 2024)
The management of the brown stink bug, Euschistus heros Fabricius (Hemiptera: Pentatomidae), which is one of the main pests in soybean crops in Brazil, based on applied biological control programs, depends on detailed knowledge of the biological, behavioral parameters and capacity dispersion of control agents in agroecosystems. Only after approval of the reference forecast by the Ministry of Agriculture, livestock and supply for registration, a mandatory process in Brazil, is it possible to commercialize the biological agent. From this stage onwards, it is expected that studies will improve the optimization of technological packages to guarantee the efficiency and suitability of a macrobiological agent. This is the case of the egg parasitoid of pentatomids, Telenomus podisi Ashmead (Hymenoptera: Scelionidae). As a consequence of the use without technical and successive positioning of chemical insecticides to control stink bugs in soybean crops, the evolution of resistant populations of this pest may occur in Brazil. Therefore, the mass release of T. podisi in large areas has been seen as a promising and relevant management technique for reducing stink bugs, as well as being a strategy for managing resistance. In this context, concepts and studies on bioecological aspects, parameters inherent to the development of a quality control for mass rearing, dispersion, and mass release of T. podisi inside integrated soybean pest management programs were explored. The knowledge contained in the literature specifically on the use of T. podisi in the field is still relatively scarce. However, it provides solid bases for the development of more assertive research in the near future and highlights gaps that need attention and clarification in the optimization of mass releases of egg parasitoids in widely cultivated crops.
Keywords: Biological control; Hemiptera; Hymenoptera; Mass rearing; Pentatomidae; Scelionidae